Airline strategy during Covid-19 outbreak: A case study from Air Asia - Dyah Nikita Sari; Nur Hayu Ramadhani; Agista Putri Prameswari (Universitas Sebelas Maret, 2021)
Corona Virus Disease 2019 (Covid-19) is an epidemic that has affected all aspects of life, especially transportation and tourism. The operational mode of transportation has strict requirements from both the passenger and operator side to carry out health protocols and support the Government's efforts to prevent the increase in the positive rate of Covid-19 with a large-scale social restriction (PSBB) policy. On the other hand, these regulations impact the decisions of tourists and passengers to postpone or even cancel their trips. So this research was conducted with qualitative descriptive analysis method by describing the object of research based on related data and information. In general, this description can explain the phenomena relating to how AirAsia Indonesia is dealing with the Covid-19 pandemic. The data are taken from the World Health Organization (WHO), the Central Statistics Agency on tourism and transportation developments in Indonesia, and the AirAsia Indonesia Annual Report. The results found that there was a decrease in passengers, both domestic and International, due to the Covid-19 pandemic. So AirAsia Indonesia's strategy is to maintain the Company's performance by launching Unlimited passes, AVA Chatbot, Super ASEAN, and opening six new flight routes.